Comparative study of kinematics and muscle activity between elite and amateur table tennis players during topspin loop against backspin movements - Wang, M.; Fu, L.; Gu. Y.; Mei, Q.; Fu, F.; Fernandez, J. (Journal of Human Kinetics, 2018)
This study investigated differences of lower limb kinematics and muscle activity during table tennis topspin loop against backspin movements between elite players (EPs) and amateur players (APs). Ten EPs and ten APs performed crosscourt backhand loop movements against the backspin ball with maximal power. Vicon motion analysis and a MEGA ME6000 system was used to capture kinematics and surface EMG data. The motion was divided into two phases, including the backswing and swing. The joints` flexion and extension angle tendency between EPs and APs differed significantly. The coefficient of multiple correlation (CMC) values for EPs were all beyond 0.9, indicating high similarity of joint angles change. APs presented moderate similarity with CMC values from 0.5 to 0.75. Compared to APs, EPs presented larger ankle eversion, knee and hip flexion at the beginning moment of the backswing. In the sEMG test, EPs presented smaller standardized AEMG (average electromyography) of the lower limb muscles in the rectus femoris and tibia anterior on both sides. Additionally, the maximum activation of each muscle for EPs was smaller and MPF (mean power frequency) of the lower limb was greater during the whole movement. The present study revealed that EPs could complete this technical motion more economically than APs, meanwhile, EPs were more efficient in muscle usage and showed better balance ability.